2013
DOI: 10.1073/pnas.1301353110
|View full text |Cite
|
Sign up to set email alerts
|

Distinct patterns of functional brain connectivity correlate with objective performance and subjective beliefs

Abstract: The degree of correspondence between objective performance and subjective beliefs varies widely across individuals. Here we demonstrate that functional brain network connectivity measured before exposure to a perceptual decision task covaries with individual objective (type-I performance) and subjective (type-II performance) accuracy. Increases in connectivity with type-II performance were observed in networks measured while participants directed attention inward (focus on respiration), but not in networks mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…On the other hand, interoceptive awareness and metacognition are intimately related. Focus on internal visceral signals and constant monitoring and feedback updating of internal predictions are important for the construction of subjective feeling states, and their disruption could explain the patients' behavioural failures [11,70,71]. In this sense, previous reports show that BA10 (i) supports emotional processing of internal states [72], (ii) is related to information retrieval and prospective memory [72] and (iii) could contribute to anosognosia, a typical symptom of dementias [30].…”
Section: (C) Interoceptive Awarenessmentioning
confidence: 98%
“…On the other hand, interoceptive awareness and metacognition are intimately related. Focus on internal visceral signals and constant monitoring and feedback updating of internal predictions are important for the construction of subjective feeling states, and their disruption could explain the patients' behavioural failures [11,70,71]. In this sense, previous reports show that BA10 (i) supports emotional processing of internal states [72], (ii) is related to information retrieval and prospective memory [72] and (iii) could contribute to anosognosia, a typical symptom of dementias [30].…”
Section: (C) Interoceptive Awarenessmentioning
confidence: 98%
“…It has been proposed that the anterior prefrontal cortex (corresponding to the OFC, the fronto-polar cortex, and dorso-medial PFC) could be involved in this process (Barttfeld et al, 2013;Kepecs et al, 2008;Lak et al, 2014;Middlebrooks and Sommer, 2012;Yokoyama et al, 2010). De Martino and colleagues (De Martino et al, 2013) showed that in value-based decisions in humans, the ventromedial prefrontal cortex (vmPFC) conveys mixed information about value and confidence, hence providing an implicit code of confidence.…”
Section: Optimization Of Information-seekingmentioning
confidence: 99%
“…Previous research showed that healthy adults differ in their metacognitive accuracy [40], in their tendency to be under or overconfident, and in the shape of their distribution of confidence ratings [41]. These features were linked to individual differences in brain structure [40], function [42], and personality trait [41]. For example, scoring high in optimism correlates with the tendency to be overconfident [41].…”
Section: Origins and Function Of Post-decisional Biasesmentioning
confidence: 99%